IMPAS: Modification of the PAS Questionnaire to Measure Attitudes of High School Students towards Physics in Indonesia - Fatah Kurniawan; Achmad Samsudin; Didi Teguh Chandra; Endang Sriwati; Bayram Coştu (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2023)
This study aims to develop an instrument that measures students' attitudes toward physics ang to test its validity and reliability. This instrument was a result of a modification from the PAS Questionnaire, namely IMPAS. This research novelty is making a new instrument that solves the shortcomings in PAS Questionnaire. So, this instrument can be used by teachers and researcers in Indonesia. The target of this IMPAS Questionnaire will be high school students in Indonesia. Using the ADDIE research model, the IMPAS Questionnaire was successfully developed and tested on 156 high school students. The IMPAS Questionnaire consists of 24 positive, negative, neutral positive, and neutral negative statements. The results of the CVR analysis and the Rasch model provide an understanding that the IMPAS Questionnaire has good content and construct validity. So, the IMPAS Questionnaire can be stated to have the ability to measure students' attitudes toward physics accurately. In addition, the results of the Rasch model analysis provide an understanding that the IMPAS Questionnaire has a moderate person reliability, excellent item reliability, and good internal consistency. Therefore, the IMPAS Questionnaire can be stated to have sufficient consistency in measuring students' attitudes toward physics. Thus, the development of an instrument to measure students' attitudes toward physics has been done successfully. Hopefully, this research can contribute to Indonesian education, especially to physics teachers and physics education researchers.